Design and Implementation of Unity-based Special Unmanned Vehicle Operating Simulator - Chen, Yiming; Gao, Jiaxin; Gao, Shiwang; Li, Chuanqi (International Journal of Computer Science and Information Technology, 2024)
Special unmanned vehicles can replace personnel to perform military tasks with high risk coefficients, such as long-distance reconnaissance, guided irradiation, and weapons strikes. In order to ensure that the special unmanned vehicle can quickly and accurately complete the established task action, the operator should carry out a large number of trainings in advance for the task content, if the training is directly used in the early stage of the training to manipulate the training, which has the security risks, it’s easy to increase the operator's psychological pressure, and the actual training site can't realistically restore the task scene, the training effect is also single. In view of the above problems, this paper designs a special unmanned vehicle control simulator, which enables the trainers to intuitively understand the task content and key points, and at the same time can control the unmanned vehicle in the virtual task environment to carry out the established task training and result review and analysis, so as to rapidly improve the control level of the trainers and ensure the successful completion of the established task.